2023
DOI: 10.1083/jcb.202206058
|View full text |Cite
|
Sign up to set email alerts
|

Meiotic resetting of the cellular Sod1 pool is driven by protein aggregation, degradation, and transient LUTI-mediated repression

Abstract: Gametogenesis requires packaging of the cellular components needed for the next generation. In budding yeast, this process includes degradation of many mitotically stable proteins, followed by their resynthesis. Here, we show that one such case—Superoxide dismutase 1 (Sod1), a protein that commonly aggregates in human ALS patients—is regulated by an integrated set of events, beginning with the formation of pre-meiotic Sod1 aggregates. This is followed by degradation of a subset of the prior Sod1 pool and clear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 68 publications
1
1
0
Order By: Relevance
“…In ΔLUTI cells, we observed an increase in the abundance of SWI4 canon mRNA (Figure 5E). This finding corroborates previous reports, where LUTI expression leads to co-transcriptional silencing of the canonical gene promoter, thereby silencing expression of the protein-coding transcript (Chen et al, 2017; Chia et al, 2017; Van Dalfsen et al, 2018; Tresenrider et al, 2021; Vander Wende et al, 2022). Finally, by immunoblotting, we observed an increase in Swi4 protein abundance in the ΔLUTI mutant compared to wild type (Figure 5E and 5F), further indicating that SWI4 LUTI expression downregulates Swi4 protein levels in meiosis.…”
Section: Resultssupporting
confidence: 93%
“…In ΔLUTI cells, we observed an increase in the abundance of SWI4 canon mRNA (Figure 5E). This finding corroborates previous reports, where LUTI expression leads to co-transcriptional silencing of the canonical gene promoter, thereby silencing expression of the protein-coding transcript (Chen et al, 2017; Chia et al, 2017; Van Dalfsen et al, 2018; Tresenrider et al, 2021; Vander Wende et al, 2022). Finally, by immunoblotting, we observed an increase in Swi4 protein abundance in the ΔLUTI mutant compared to wild type (Figure 5E and 5F), further indicating that SWI4 LUTI expression downregulates Swi4 protein levels in meiosis.…”
Section: Resultssupporting
confidence: 93%
“…Case studies have revealed that diverse gene targets are subject to LUTI-based repression, including the genes encoding the kinetochore subunit Ndc80 (J. Chen et al, 2017;Chia et al, 2017), the superoxide dismutase enzyme Sod1 (Vander Wende et al, 2023), the transcription factor Swi4 (Su et al, 2023), and the purine hydrolase enzyme Hnt1 (Van Dalfsen et al, 2018;Tatip et al, 2020). Importantly, the observation that the human protooncogene MDM2 is subject to LUTI-based interference has revealed this form of gene repression is broadly conserved (Hollerer et al, 2019).…”
Section: Introductionmentioning
confidence: 99%